The sustainable chef the environment in culinary arts, restaurants, and hospitality - Gössling, Stefan; Hall, C. Michael (Routledge, Taylor & Francis Group, 2022)
"This book provides the first systematic and accessible text for students of hospitality and the culinary arts that directly addresses how more sustainable restaurants and commercial food services can be achieved. Food systems receive growing attention because they link various sustainability dimensions. Restaurants are at the heart of these developments, and their decisions to purchase regional foods, or to prepare menus that are healthier and less environmentally problematic have great influence on food production processes. This book is systematically designed around understanding the inputs and outputs of the commercial kitchen as well as what happens in the restaurant from the perspective of operators, staff and the consumer. The book considers different management approaches and further looks at the role of restaurants, chefs and staff in the wider community and the positive contributions that commercial kitchens can make to promoting sustainable food ways. Case studies from all over the world illustrate the tools and techniques helping to meet environmental and economic bottom lines. This will be essential reading for all students of hospitality and the culinary arts"--